2021
DOI: 10.3390/v13050726
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory CEA Cell Adhesion Molecule 6 (CEACAM6/CD66c) Is a Protein Receptor for the Influenza A Virus

Abstract: To establish a productive infection in host cells, viruses often use one or multiple host membrane glycoproteins as their receptors. For Influenza A virus (IAV) such a glycoprotein receptor has not been described, to date. Here we show that IAV is using the host membrane glycoprotein CD66c as a receptor for entry into human epithelial lung cells. Neuraminidase (NA), a viral spike protein, binds to CD66c on the cell surface during IAV entry into the host cells. Lung cells overexpressing CD66c showed an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The treatment of anti-sialylated glycoprotein CD83 on dendritic cells and macrophages could reduce influenza A virus-lung injury and in mice [ 37 ]. Influenza A virus can also use a host adhesion molecule on surface CD66c as a novel receptor that binds to viral NA during entry into A549 and HEK293 cells [ 38 ]. Since both of them have immune functions and present on primary human T cells, the exploration of their roles in early infection with the influenza A virus should be taken seriously for some time to come.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of anti-sialylated glycoprotein CD83 on dendritic cells and macrophages could reduce influenza A virus-lung injury and in mice [ 37 ]. Influenza A virus can also use a host adhesion molecule on surface CD66c as a novel receptor that binds to viral NA during entry into A549 and HEK293 cells [ 38 ]. Since both of them have immune functions and present on primary human T cells, the exploration of their roles in early infection with the influenza A virus should be taken seriously for some time to come.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study has shown that IAV does not directly bind to EGFR, but the binding of IAV with multivalent sialic acid clusters can trigger EGFR activation ( 56 ). However, the glycoprotein carcinoembryonic antigen-related cell adhesion molecule 6 (CD66c or CEACAM6) has recently been identified as a receptor for IAV infection ( 57 ), and further research will undoubtedly identify more such interacting receptors in the future. After binding to cellular receptors, IAV is taken up by cells via either clathrin- or caveolin-dependent endocytosis, which usually occurs at lipid rafts ( Figure 1 ) ( 50 , 58 ).…”
Section: Iav Internalization Relies On Lipid Raftsmentioning
confidence: 99%
“…Thus, M59 was associated with severe in uenza development. M59 hub gene CEACAM6 has been reported as a protein receptor for the in uenza A virus [24].…”
Section: Module Expression Was Changed In Severe a (H1n1) Pandemic In...mentioning
confidence: 99%